Personal and political networks in 1917: Vladimir Zenzinov and the Socialist Revolutionary Party - Badcock, Sarah (Brill, 2016)
This article explores the place of individuals, ideologies and personal and political networks in shaping the larger political landscape in revolutionary Russia. The shape and culture of the Socialist Revolutionary Party (psr) will be at the heart of my anal- ysis of coalition politics. I focus particularly on the personal and political networks surrounding Vladimir Mikhailovich Zenzinov during 1917. This analysis suggests that the shape of coalition politics in 1917 was defined in part by pre-revolutionary social and political networks, and that these to some extent transcended party political affiliations. While the nature of coalition politics necessitated this political fluidity, it is nevertheless worth emphasizing, because the discourse around 1917 is often framed along explicitly party political lines.